2021
DOI: 10.1016/j.neuroimage.2020.117410
|View full text |Cite
|
Sign up to set email alerts
|

A distributed dynamic brain network mediates linguistic tone representation and categorization

Abstract: Successful categorization requires listeners to represent the incoming sensory information, resolve the “blooming, buzzing confusion” inherent to noisy sensory signals, and leverage the accumulated evidence towards making a decision. Despite decades of intense debate, the neural systems underlying speech categorization remain unresolved. Here we assessed the neural representation and categorization of lexical tones by native Mandarin speakers ( N = 31) across a range of acoustic and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 76 publications
(88 reference statements)
2
9
0
Order By: Relevance
“…We found a dorsal auditory-motor pathway consisting of the left superior temporal gyrus (STG), supramarginal gyrus (SMG), anterior inferior parietal lobule (IPLa), and precentral gyrus (PreCG) shows increasing representations of perceptual category distance. This auditory-category representational network is consistent with a broad speech processing network, spanning the frontal, temporal, and parietal lobes (Feng et al, 2021;Giraud and Poeppel, 2012;Hickok and Poeppel, 2007;Rauschecker and Scott, 2009). Among these brain regions, the STG has been demonstrated to encode multidimensional acoustic signals (including spectral and temporal modulation) that differentiate native speech categories (Arsenault and Buchsbaum, 2015;Bonte et al, 2014;Feng et al, 2016;Feng et al, 2018;Formisano et al, 2008;Mesgarani et al, 2014), which is presumably acquired slowly with the development of one's native language.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…We found a dorsal auditory-motor pathway consisting of the left superior temporal gyrus (STG), supramarginal gyrus (SMG), anterior inferior parietal lobule (IPLa), and precentral gyrus (PreCG) shows increasing representations of perceptual category distance. This auditory-category representational network is consistent with a broad speech processing network, spanning the frontal, temporal, and parietal lobes (Feng et al, 2021;Giraud and Poeppel, 2012;Hickok and Poeppel, 2007;Rauschecker and Scott, 2009). Among these brain regions, the STG has been demonstrated to encode multidimensional acoustic signals (including spectral and temporal modulation) that differentiate native speech categories (Arsenault and Buchsbaum, 2015;Bonte et al, 2014;Feng et al, 2016;Feng et al, 2018;Formisano et al, 2008;Mesgarani et al, 2014), which is presumably acquired slowly with the development of one's native language.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies have found that the IFG is involved in the acquisition of auditory or non-native speech categories (Lee et al, 2012;Myers, 2014;Myers and Swan, 2012) with response patterns in this region showing greater sensitivity to between-category changes and reduced sensitivity to within-category changes after training. To achieve successful learning, the IFG is hypothesized to work dynamically with the temporal cortices (e.g., STG) to form categorical representations and make overt categorization decisions (Feng et al, 2021;Myers, 2014;Myers et al, 2009;Myers and Swan, 2012). Here we demonstrate that different sub-regions of the IFG showed distinct profiles of plasticity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Nativeness in Neural Representational Structure Predicts Sound-to-Category Learning Success It has been previously demonstrated that task-general and acoustic-invariant neural representations of Mandarin tone categories for native listeners are evidenced in the superior temporal areas and inferior parietal lobule using multivariate pattern classification (Feng, Gan et al, 2018;Feng et al, 2021). While this classification approach reveals category-level representations, this analytic method cannot capture the fine representational structures underlying the neural activation patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The same searchlight RSA was also conducted for native speakers for comparison. This searchlight approach has been described extensively in previous studies (Feng, Gan et al, 2018;Feng et al, 2019Feng et al, , 2021. We briefly described the approach here.…”
Section: Model-based Rsa and Searchlight Approachmentioning
confidence: 99%